2016
DOI: 10.1186/s12967-016-0863-3
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin could be a potential biomarker for acute appendicitis

Abstract: BackgroundAcute appendicitis is a common cause for a visit to the emergency department and appendectomy represents the most common emergency procedure in surgery. The rate of negative appendectomy however has remained high despite modern diagnostic apparatus. Therefore, there is need for a better preoperative screening of patients with suspected appendicitis. Calprotectin represents a predominant protein in the cytosol of neutrophil granulocytes and has been extensively investigated with regard to bowel pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 18 publications
1
24
0
1
Order By: Relevance
“…Immunohistochemical activity was determined in epithelial and inflammatory cells in consideration of the amount of inflammatory cells within the lumen of the vermiform appendix. As reported previously, specimens with confirmed appendicitis stained positive, Fig 1 , while control specimens without appendicitis (from patients following right hemicolectomy) stained negative, Fig 2 [18]. …”
Section: Methodssupporting
confidence: 69%
See 3 more Smart Citations
“…Immunohistochemical activity was determined in epithelial and inflammatory cells in consideration of the amount of inflammatory cells within the lumen of the vermiform appendix. As reported previously, specimens with confirmed appendicitis stained positive, Fig 1 , while control specimens without appendicitis (from patients following right hemicolectomy) stained negative, Fig 2 [18]. …”
Section: Methodssupporting
confidence: 69%
“…In a previous paper, the qualitative expression of Cal in appendectomy specimens was examined via immunohistochemistry using specific anti-calprotectin antibodies [18]. Strong reactions were seen in specimens with proven appendicitis following histopathology, while no reaction was observed in non-inflamed vermiform appendix specimens from patients following right sided hemicolectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, numerous ongoing studies investigate the relationship of the FC levels with various bowel diseases, such as acute appendicitis, Henoch‐Schönlein purpura, and colonic polyps . Several studies showed that even neonates who suffered from necrotizing enterocolitis had early elevation in FC levels .…”
Section: Discussionmentioning
confidence: 99%